2017
DOI: 10.1007/s00246-016-1553-x
|View full text |Cite
|
Sign up to set email alerts
|

Perimembranous Ventricular Septal Defect Device Closure: Choosing Between Amplatzer Duct Occluder I and II

Abstract: Transcatheter closure of perimembranous ventricular septal defects (pmVSDs) is a well-established procedure. Recently, Amplatzer duct occluders (ADO) I and II have been reported to close large series of pmVSDs successfully (off-label use). ADOs are economical compared with the standard Amplatzer VSD occluders, a major consideration in developing countries with low-budget programs. We report closure of symptomatic, hemodynamically significant pmVSDs using the ADOI and ADOII devices. Although there are no set cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
3
23
0
2
Order By: Relevance
“…Dilawar et al [20] informed that VSD closure rate was 100% (7/7) using ADO immediately after the procedure, and medium term follow-up of 6/7 patients revealed no residual VSD with 100% success. El-Sisi et al [26] in a prospective observational single center study of 30 patients reported a 100% success using ADO devices (I and II). Ghaderian et al [25] used an ADO device in 28 patients with a successful rate of 96.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Dilawar et al [20] informed that VSD closure rate was 100% (7/7) using ADO immediately after the procedure, and medium term follow-up of 6/7 patients revealed no residual VSD with 100% success. El-Sisi et al [26] in a prospective observational single center study of 30 patients reported a 100% success using ADO devices (I and II). Ghaderian et al [25] used an ADO device in 28 patients with a successful rate of 96.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the procedure success rate was high in both groups (95.6% in the DO group vs. 97.2%in the Coil group, P 5 .53) and comparable to other studies using conventional, off-label use or new devices for percutaneous pmVSD closure. [8][9][10][11][12][13][14][26][27][28][29] In contrast, the clo- [30][31][32][33] Thus, percutaneous VSD closure has been largely abandoned in many countries, and surgical closure is still accepted as the standard therapy for pmVSD. Patients in whom CHB was first detected after percutaneous VSD closure in our centers were treated with intense medication, including corticosteroids, temporary pacemaker and continuously followed for two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…2 Nowadays, transcatheter device closure for perimembranous ventricular septal defect has become a widely accepted alternative to openheart surgery. [3][4][5][6] Since the development of occluders and intervention technique, the spectrum of indications has been widened. Recently, several studies on the transcatheter device of ventricular septal defect using Amplatzer duct occluder 2 have been reported.…”
mentioning
confidence: 99%
“…Recently, several studies on the transcatheter device of ventricular septal defect using Amplatzer duct occluder 2 have been reported. [6][7][8][9] However, most of the reports were based on small samples without a long-term follow-up. The appropriate time of usage and ventricular septal defect size capable of closure, the accurate indications, and long-term results of Amplatzer duct occluder 2 were not yet clarified.…”
mentioning
confidence: 99%